Photonic Crystals Physics and Practical Modeling - Sukhoivanov, Igor A.; Guryev, Igor V. (Springer Series in Optical Sciences, 2009)
The great interest in photonic crystals and their applications in the past decade requires a thorough training of students and professionals who can practically apply the knowledge of physics of photonic crystals together with skills of independent calculation of basic characteristics of photonic crystals and modelling of various photonic crystal elements for application in all-optical communication systems. This book combines basic backgrounds in fiber and integrated optics with detailed analysis of mathematical models for 1D, 2D and 3D photonic crystals and microstructured fibers, as well as with descriptions of real algorithms and codes for practical realization of the models.